Benzocaine-Induced Methemoglobinemia in a Postoperative Bariatric Patient following Esophagogastroduodenoscopy - Khuram Khan; Irwin White-Gittens; Saqib Saeed; Leaque Ahmed (Case Reports in Critical Care)
Methemoglobinemia is a rare complication in clinical practice. It is most commonly seen in patients undergoing endoscopic procedures, including EGDs, laryngoscopies, bronchoscopies, and nasogastric tube insertions. This is thought to be a disease seen almost exclusively in patients with genetic predispositions to develop it; the increasing use of topical anesthetics during procedures has made methemoglobinemia a disease entity that every clinical provider should be able to recognize and treat. Clinically, patients become cyanotic with mild oxygen derangements on pulse oximetry, in the range of 84 to 90%. Paradoxically, these patients demonstrate normal to supranormal oxygen levels in the blood on blood gas analysis. We report a case of 34-year-old female postoperative Roux-en-Y gastric bypass patient who developed hypoxia and cyanosis after a routine EGD procedure to relieve a food impaction. Differentials of aspiration and pulmonary embolism were plausible; stat blood gas analysis clinched the diagnosis and managed with intravenous methylene blue.